Radiative Effects and Optical Properties of Aerosol during Two Dust Events in 2013 over Zanjan, Iran ... : التأثيرات الإشعاعية والخصائص البصرية للهباء الجوي خلال حدثين للغبار في عام 2013 فوق زنجان، إيران ... - Maryam Gharibzadeh; Khan Alam; A. A. Bidokhti; Yousefali Abedini; Amir Masoumi (OpenAlex, 2017)
Aerosol optical propertieslike Aerosol Optical Depth (AOD), Angstrom Exponent (AE), ASYmmetry parameter(ASY), Single Scattering Albedo (SSA), and Aerosol Volume Size Distribution(AVSD) have been analyzed for the atmosphere of Zanjan, a city in NorthwestIran. These properties have been studied usingthe ground-based AErosol RObotic NETwork (AERONET)duringthe periods from 8 to18 May and 8 to 14 June, 2013. During thestudy period, 14th May and 10th June are identified asdusty days, and AOD at 500 nm reached a peak value of 0.64 and 0.80, on thesedays. The high values of AOD and low values of AE during dusty days illustratethat coarse mode particles like dust are dominant. In the visible spectrum ASY usually decreasesand then somewhat increases in the near infrared region. Both SSA and AVSD suggest predominance of coarseparticles on the dusty days. The Santa Barbara DISORT AtmosphericRadiative Transfer (SBDART) model is utilized to simulate the solar irradiancevalues for the above-mentioned periods at the earth's ... : تم تحليل الخصائص البصرية للهباء الجوي مثل العمق البصري للهباء الجوي (AOD)، وأسس الأنجستروم (AE)، ومعلمة ASYmmetry (ASY)، والبياض أحادي التشتت (SSA)، وتوزيع حجم الهباء الجوي (AVSD) لجو زنجان، وهي مدينة في شمال غرب إيران. تمت دراسة هذه الخصائص باستخدام شبكة AErosol RObotic NETwork الأرضية (AERONET)خلال الفترات من 8 إلى 18 مايو ومن 8 إلى 14 يونيو 2013. خلال فترة الدراسة، تم تحديد 14 مايو و 10 يونيو كأيام متربة، ووصلت AOD عند 500 نانومتر إلى ذروة قيمة 0.64 و 0.80، في تلك الأيام. توضح القيم العالية لـ AOD والقيم المنخفضة لـ AE خلال الأيام المتربة أن جزيئات الوضع الخشن مثل الغبار هي السائدة. في الطيف المرئي، عادة ما ينخفض ASY ثم يزيد إلى حد ما في منطقة الأشعة تحت الحمراء القريبة. تشير كل من SSA و AVSD إلى هيمنة الجسيمات الخشنة في الأيام المغبرة. يستخدم نموذج الانتقال الإشعاعي للغلاف الجوي لسانتا باربرا ديزورت (SBDART) لمحاكاة قيم الإشعاع الشمسي للفترات المذكورة أعلاه على سطح الأرض، داخل الغلاف الجوي، وفي الجزء العلوي من الغلاف الجوي (TOA). تظهر النتائج أن أنواع الهباء الجوي السائدة هي جزيئات الغبار التي لها تأثير ...